Zero Waste Knowledge and Behavior of Early Childhood Pre-Service Teacher in Science Education - Rohimi Zamzam; Ati Kusmawati; Ilmi Zajuli Ichsan; Putri Ratih Puspitasari (Jurnal Penelitian Pendidikan IPA, 2023)
The importance of environmental education needs to be integrated with science learning related to zero waste topics. Environmental topics related to zero waste need to be understood by early childhood pre-service teachers because teachers are an important subject in providing understanding to young children regarding the environment. This research aims to describe environmental knowledge and zero waste behavior in early childhood pre-service teachers. The method used in this research is a descriptive method through data collection techniques using surveys. The instruments used in this research were 2 types, namely test questions used to measure environmental knowledge and questionnaires used to measure zero waste behavior. The results of this research show that the average zero waste knowledge score of early childhood pre-service teachers is still in the very low category (32.87). The average zero waste behavior score for early childhood pre-service teachers is in the moderate category (65.83). The results of this research show how important environmental education related to zero waste is integrated with science education. The recommendation from this research is to be able to develop media that can be integrated into zero-waste learning.